2021
DOI: 10.1016/j.adolescence.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of familial warmth and LGBTQ+ specific family rejection on LGBTQ+ adolescents’ self‐esteem

Abstract: Our study sought to assess the interplay of family dynamics, namely familial warmth and LGBTQ+ specific rejection, and its association to self-esteem in a non-probabilistic sample of LGBTQ+ adolescents in the United States. Methods: Stratified by (1) cisgender and (2) transgender and non-binary LGBTQ+ adolescents (N = 8774), we tested multivariable regression analyses to assess the association between familial warmth and LGBTQ+ specific family rejection, adjusted for sociodemographic characteristics. We then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 140 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…In another study that highlighted the importance of "being out", family rejection moderated the relationship between family warmth and self-esteem in a sample of 8774 adolescents [9]. In a survey on 129 adolescents, less positive initial feelings were noted for trans masculine than trans feminine adolescents by mothers and fathers at 25% vs 36% averaged across parents, although the increase in acceptance was greater for trans masculine adolescents [10].…”
Section: Parental Rejectionmentioning
confidence: 94%
“…In another study that highlighted the importance of "being out", family rejection moderated the relationship between family warmth and self-esteem in a sample of 8774 adolescents [9]. In a survey on 129 adolescents, less positive initial feelings were noted for trans masculine than trans feminine adolescents by mothers and fathers at 25% vs 36% averaged across parents, although the increase in acceptance was greater for trans masculine adolescents [10].…”
Section: Parental Rejectionmentioning
confidence: 94%
“…An exploratory study found no associations between gender minority stress and resilience scales and circulating concentrations of CRP in young trans persons receiving GAHT ( 279 , 280 ). Notably, 84% of these older teenagers and young adult participants lived with their parents, indicative of stable familial support, perhaps suggesting that a supportive familial structure is “anti-inflammatory” in an otherwise “pro-inflammatory” society ( 281 , 282 ). These observational studies highlight the importance of family support for psychological wellbeing as well as for material survival (adequate health insurance might only be possible through parents or spouses, financial security through social security income relies on traditional family structures).…”
Section: Environmental Exposure: Impacts Of Chronic Social Stressmentioning
confidence: 99%
“…Furthermore, perceptions of family connectedness have declined for lesbian, gay, and bisexual (LGB) youth, relative to heterosexual youth, from 1998 to 2013 (Watson et al, 2019). Family members’ reactions to LGBTQ youths’ identity have important implications for that young person’s well-being, such that positive reactions predict better physical and emotional well-being (Ryan et al, 2010), whereas negative reactions are associated with a greater incidence of attempted suicide, substance use, unprotected sex, higher levels of depression, and lower self-esteem (Meanley et al, 2021; Ryan et al, 2009).…”
Section: Perceived Family Reactions To Youth Lgbtq Identitymentioning
confidence: 99%
“…Family members’ reactions to youth LGBTQ identity have been found to predict a range of important youth outcomes. Family reactions that are positive (assessed through youth report of parent/caregiver behavior) predict greater self-esteem, social support, and better physical health for LGBT young adults (Meanley et al, 2021; Ryan et al, 2010), whereas negative reactions are associated with greater incidence of attempted suicide, illegal substance use, unprotected sex, and higher levels of depression for LGB young adults (Ryan et al, 2009), as well as lower self-esteem (Meanley et al, 2021). Similar results have been found for transgender and gender diverse youth; youth who perceive their parents as supportive of their identity report higher life satisfaction, self-esteem, and fewer depressive symptoms (de Vries et al, 2016).…”
Section: Perceived Family Reactions To Youth Lgbtq Identitymentioning
confidence: 99%